People's Republic of China : 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, China's economic developments and policies are discussed. Economic growth has been increased by expanding infrastructure and real estate construction. The policy measures outlined in the twelfth five-year plan and implementation of financial reform are important for China's balanced global growth. The price-based tools of monetary policy, improvement over monetary policy framework, and interest rate structure are encouraged. The financial sector assessment program and the importance of well-sequenced financial liberalization and reforms, which are part of China's rebalancing strategy, are ascribed.